Social Capital and Health Inequality in European Welfare States - Rostila, M.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2013)
Drawing on cross-national European data from the European Social Survey as well as Swedish national survey data and registers, this book investigates social capital in relation to health and health inequalities in European welfare states.
Keywords: Social policy; Welfare state; Political sociology; Public administration; Social service .; Political science; Social Policy; Politics of the Welfare State; Political Sociology; Public Administration; Social Care; Political Science